Integrated metabolome and transcriptome analysis provide insight into the biosynthesis of flavonoids in Panax japonicus - Chen, ChunYu; Wang, Ping; Yan, Yan; Jiao, ZeWei; Xie, ShuHao; Li, Ye; Di, Peng (Frontiers in Plant Science, 2024)
Panax japonicus is an important medicinal plant, and flavonoids are one of its main secondary metabolites. In this study, the main roots, fibrous roots, stems, leaves and flowers of P. japonicus were analyzed using transcriptomics and widely targeted metabolomics. Through correlation analysis of transcription and metabolism, the flavonoid biosynthesis pathway in P. japonicus was analyzed, and the accumulation of flavonoid metabolites and the expression of related genes were investigated. Metabolomics revealed a total of 209 flavonoid metabolites in P. japonicus, among which flavonoids, flavonols, flavanones and flavanonols significantly accumulated in the flowers and leaves. Transcriptome sequencing revealed that key genes in the flavonoid pathway exhibited increased expression in the flowers and leaves. The expression patterns of key genes involved in flavonoid biosynthesis, including PjC4H, Pj4CL, PjCHS, PjCHI, PjF3H, PjF3'H, PjCYP, and PjPAL, are consistent with their upstream and downstream metabolites, demonstrating a significant positive correlation among them. In addition, the PjUGT gene is highly expressed in five tissues of P. japonicus, indicating that PjUGT is one of the key factors for the diversity of flavonoid glycosides. The WGCNA results showed that WRKY transcription factors exist widely in the candidate modules, and it was possible that PjWRKY transcription factors are involved in regulating the expression of key genes involved in flavonoid biosynthesis and the biosynthesis of flavonoid metabolites. This study reveals spatial differences in the accumulation patterns of flavonoid metabolites in different tissues and provides important clues for further understanding the regulatory mechanisms of flavonoid metabolism in P. japonicus, thus contributing to the optimization of germplasm resources of P. japonicus and the promotion of genetic diversity analysis.